1975
DOI: 10.1111/j.1432-1033.1975.tb04044.x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of Highly Purified Globin Messenger RNA from Anaemic-Rabbit Spleen

Abstract: Highly purified globin messenger RNA has been isolated from the erythropoietic spleen of anaemic rabbits. This RNA, which sediments at 9‐S, directs the synthesis of α and β rabbit globin chains in a Krebs II ascites cell‐free system. Globin accounts for more than 90% of the cell‐free synthesized proteins. Spleen 9‐S RNA is, however, about 30% less effective on a weight basis than blood reticulocyte 9‐S RNA in directing globin synthesis in the cell‐free system. When analysed on polyacrylamide gels, spleen 9‐S R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

1975
1975
1987
1987

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 26 publications
2
3
0
Order By: Relevance
“…3). The overall decrease in size upon digestion is consistent with recent estimates of the average poly(A) size in this message (23).…”
Section: Discussionsupporting
confidence: 90%
“…3). The overall decrease in size upon digestion is consistent with recent estimates of the average poly(A) size in this message (23).…”
Section: Discussionsupporting
confidence: 90%
“…We employed the method described by Bishop et al (1974) since this is a method which is well characterized stoichiometrically. We have confirmed that a one to one ribonuclease-resistant hybrid between poly(A) and radioactive poly(U) was formed (Figure 1), contrary to what some authors have reported (Nokin et al, 1975), under similar experimental conditions.…”
Section: Resultssupporting
confidence: 78%
“…lose-retained RNA was further bound to a poly(U) -Sepharose column. Three fractions were obtained: (i) unbound; (ii) bound and eluted in low salt at 20 C; (iii) bound and eluted in low salt at 45 C, according to Nokin et al (28). After chromatography of the active mRNA preparation on poly(U)-Sepharose, the three fractions obtained were assayed in the wheat germ system and 35S-labeled products were analyzed as before by polyacrylamide gel electrophoresis.…”
Section: Fpv Structural Proteinsmentioning
confidence: 99%